New developments in piezoelectric polymerie composite materials for environmental energy usages - Pal V.; Singh A.K.; Swain P.K. (My University, 2025)
Harvesting of energy remains a subject under great attention and this chapter provides a general idea of a different kind of energy harvesting mechanism utilized by piezoelectric polymeric composite materials. The basic phenomenon of piezoelectric materials with all relevant equations is described herein and explained as well. A recent progress of various piezoelectric polymeric composite materials is summarized with the sequence of investigations and to compare their performances in order to involve them in the environmental energy applications. An in-depth report on detailing how to drastically enhance the unique, multifunctional properties of piezoelectric polymeric composite materials with the incorporation of carbon-based nanomaterials on metal/ceramic matrix is also provided, followed by the brief details of an advance developed Pb-free piezoelectric material that shows a potential candidate for utilization in non-toxic polymeric composite materials. A comprehensive portrayal of the progress of polymeric composite materials in terms of nanogenerator design is also discussed additionally. Finally, the chapter is concluded with the future perspectives and challenges in the performance of piezoelectric polymeric composite materials. © 2023 World Scientific Publishing Company. All rights reserved.